2014
DOI: 10.1124/jpet.114.218339
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Modulation of Paracellular Claudin-5 Expression in Mouse Brain Endothelial Cells Is Mediated through the Phosphoinositide-3-Kinase/AKT Pathway

Abstract: Blood-brain barrier (BBB) integrity is compromised in many central nervous system disorders. Complex astrocyte and vascular endothelial cell interactions that regulate BBB integrity may be disturbed in these disorders. We previously showed that systemic administration of 3-chloropropanediol [(S)-(1)-3-chloro-1,2-propanediol] induces a transitory glial fibrillary acidic proteinastrocyte loss, reversible loss of tight junction complexes, and BBB integrity disruption. However, the intracellular signaling mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…At the same time, MMP-2 can also reduce the expression of claudin-5, which is the constitutive trans-membrane protein of the BBB. All of the above processes harm the structure of the BBB and lead to damage of the BBB[39]. Our experiments confirmed that the expression levels of ROCK, MLCK, and MMP2 were significantly enhanced, while the expression of claudin-5 was significantly decreased after CI/R in rats.…”
Section: Discussionsupporting
confidence: 77%
“…At the same time, MMP-2 can also reduce the expression of claudin-5, which is the constitutive trans-membrane protein of the BBB. All of the above processes harm the structure of the BBB and lead to damage of the BBB[39]. Our experiments confirmed that the expression levels of ROCK, MLCK, and MMP2 were significantly enhanced, while the expression of claudin-5 was significantly decreased after CI/R in rats.…”
Section: Discussionsupporting
confidence: 77%
“…In an earlier study, we have shown that the PI3K/AKT pathway plays a key role in modulating paracellular claudin-5 expression (Camire et al, 2014). To determine whether the PI3K/AKT pathway plays a role in cytokine/chemokine-induced loss of paracellular claudin-5 expression, we inhibited PI3K with the cell permeable inhibitor, LY294002.…”
Section: Resultsmentioning
confidence: 99%
“…This signaling pathway is activated by a number of receptors, including integrin, cytokine, G protein–coupled receptors, and intracellular signalling molecules (Gonzalez-Mariscal et al, 2008; Hemmings and Restuccia, 2012). Recently we have shown that 3-chloropropanediol (500 μM) alone induced loss of paracellular claudin-5 expression in bEnd.3 cells through the PI3K/AKT pathway (Camire et al, 2014). Pre-treating bEnd.3 cells with the selective cell-permeable PI3K inhibitor, LY294002 (25 μM), prevented TNF-α- and IL-6-induced loss of paracellular claudin-5 (Fig 6), suggesting their actions were mediated through the PI3K pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…nPKC-u, cPKC-a cPKC-b, PI3Kg, p38MAPK, MLCK and ROCK) is associated with altered claudin-5 localization and expression and ultimately TJ complex disassembly and Tyr kinase activation correlates with claudin-5 disassembly from the TJ complex. [101][102][103]106,107 Among the 23 predicted phosphorylation sites, 6 kinase-specific phosphorylation sites Thr-189, Tyr-200, Thr-207, Thr-209, Tyr-217 and Tyr-218 were observed to be present in the cytoplasmic tail region of human claudin-5. However, only one site, Thr-207, has been experimentally verified so far (RhoK and PKA) and it affects TJ integrity in murine brain endothelial cells and increases permeability.…”
Section: Phosphorylationmentioning
confidence: 99%